2015
DOI: 10.1007/s00404-015-3641-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus cyclic oral contraceptives for the treatment of endometriosis: a systematic review

Abstract: Use of oCP in a continuous fashion following conservative surgery for endometriosis is more beneficial to cyclic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 32 publications
1
28
0
5
Order By: Relevance
“…However, ''estroprogestins'' (which was the main term used in the title of the article by Muzii et al [1] ) is apparently an extremely rare term as it appears in only 15 articles in the Medline database to date (date of search: 3.11.15). Fortunately, the results and conclusions by Muzii et al [3] are in line with the rest of the evidence in the existing literature and inclusion of this study does not significantly alter the conclusions of our systematic review [2].…”
supporting
confidence: 73%
See 1 more Smart Citation
“…However, ''estroprogestins'' (which was the main term used in the title of the article by Muzii et al [1] ) is apparently an extremely rare term as it appears in only 15 articles in the Medline database to date (date of search: 3.11.15). Fortunately, the results and conclusions by Muzii et al [3] are in line with the rest of the evidence in the existing literature and inclusion of this study does not significantly alter the conclusions of our systematic review [2].…”
supporting
confidence: 73%
“…We would like to thank Dr Muzii et al [1] for their constructive comments regarding our recent systematic review [2]. Indeed, usage of a wider variety of keywords in our search strategy would have resulted to inclusion of one additional eligible multicenter, prospective, randomized trial performed by the same group of authors [3].…”
mentioning
confidence: 98%
“…The reflux of endometrial tissue via the fallopian tubes, during menstruation, and the consequent implantation of such tissue in distant places, is the prevailing theory [6]. Although endometriosis is a benign lesion, certain characteristics of it are also noted in malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…One systematic review186 showed that after conservative surgery, continuous COC use was associated with a significant reduction in dysmenorrhoea and a longer period before dysmenorrhoea recurred compared with cyclical use. One further RCT187 also reported a reduction in endometriosis-associated pelvic pain, an improvement in sexual activity and quality of life in women on a EE/dienogest continuous regimen compared to a 21/7 regimen.…”
Section: Non-contraceptive Health Benefits Associated With Chc Usementioning
confidence: 99%